Comparison of Flow Topology Between Major Groups of Airfoil with Vortex Shedding - Miasin, Rizuan; Abdullah, Aslam; Zulkafli, Mohd Fadhli (Progress in Aerospace and Aviation Technology, 2022)
The effect of vortex behavior on airfoil aerodynamic performance has been widely debated for many years, and many research studies have been conducted to examine the relationship. This paper highlights the in-depth study of flow topological processes on major airfoil groups with vortex shedding. It considers various type of corresponding geometries including symmetrical, asymmetrical, thick, and thin airfoils in order to show the differences in flow topology. The study also emphasized the behavior of separation bubbles, vortex shedding and reattachment points. The use of a commercial CFD software for the study gave reliable results within an adequate length of time. The vortex shedding were successfully highlighted either physically or hypothetically. The separation bubble was relatively easier to be identified in all cases of airfoil of interest. The evolution of separation bubble captured by the topology in the case of Eppler 169 was the unique, and involved the break of reattachment point.